1994
DOI: 10.1128/jb.176.24.7587-7600.1994
|View full text |Cite
|
Sign up to set email alerts
|

Multiple structural proteins are required for both transcriptional activation and negative autoregulation of Caulobacter crescentus flagellar genes

Abstract: The periodic and sequential expression of flagellar (fla) genes in the Caulobacter crescentus cell cycle depends on their organization into levels I to IV of a regulatory hierarchy in which genes at the top of the hierarchy are expressed early in the cell cycle and are required for the later expression of genes below them. In these studies, we have examined the regulatory role of level IIfliF operon, which is located near the top of the hierarchy. The last gene in the fliF operon, flbD, encodes a transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
1
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 72 publications
2
84
1
1
Order By: Relevance
“…1B; Ramakrishnan et al, 1994). However, some of the flagellar genes appear to be unique to C. crescentus.…”
Section: Flagellum Structure and Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…1B; Ramakrishnan et al, 1994). However, some of the flagellar genes appear to be unique to C. crescentus.…”
Section: Flagellum Structure and Assemblymentioning
confidence: 99%
“…The requirement of multiple structural genes for the regulation of the Class III and Class IV genes has suggested that flagellar gene expression in C. crescentus is co-ordinated with flagellum biosynthesis by two assembly checkpoints: transcription of Class III genes requires completion of MS ring-switch assembly, and expression of the Class IV flagellin genes requires completion of basal body-hook assembly ( Fig. 2A; Ramakrishnan et al, 1994). Similar reasoning was invoked originally to propose that completion of the basal bodyhook structure is an assembly checkpoint controlling late flagellar gene transcription in E. coli ( Fig.…”
Section: Regulation Of Class II Genesmentioning
confidence: 99%
“…Analysis of the DNA flanking the transposon insertion site revealed a high level of similarity to the fliG gene of CauZobacter crescentus (S. Moens, personal communication), which encodes a protein involved in the regulation of both the rotation and the biogenesis of the bacterial flagellum (Ramakrishnan et al, 1994). This, along with findings from the present work, indicates that even if the role of the polar flagellum in the aggregation process is not clear, both aggregation and flagellation processes could share one or more regulator genes.…”
Section: Profile Of Extracellular Proteins Of Different Strains In Himentioning
confidence: 99%
“…A potential kinase for FlbD is encoded by the £bE gene, which lies within the same operon as £bD and is required for activation of the c 54 -dependent class III and class IV promoters [25]. FlbE shares regions of homology with two-component histidine kinases and is able to phosphorylate FlbD in vitro [82].…”
Section: Control Of Late £Agellar Genes (Class III and Class Iv)mentioning
confidence: 99%